2020
DOI: 10.1371/journal.pntd.0008470
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni immunomodulatory molecule Sm16/SPO-1/SmSLP is a member of the trematode-specific helminth defence molecules (HDMs)

Abstract: Background Sm16, also known as SPO-1 and SmSLP, is a low molecular weight protein (~16kDa) secreted by the digenean trematode parasite Schistosoma mansoni, one of the main causative agents of human schistosomiasis. The molecule is secreted from the acetabular gland of the cercariae during skin invasion and is believed to perform an immune-suppressive function to protect the invading parasite from innate immune cell attack. Methodology/Principal findings We show that Sm16 homologues of the Schistosomatoidea fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Remarkably, the HDM secreted by F. hepatica (FhHDM) inhibits the development of M1 macrophages, but despite being classified in the same family of peptides, the HDM secreted by C. sinensis (CsHDM) induces an M1 phenotype (Table 1; Lund et al ., 2016; Alvarado et al ., 2017; Kang et al ., 2020). Analysis of the phylogenetic relationship of the HDM peptide family shows that while CsHDM is on the same branch as FhHDM, it is evolutionarily closer to another branch of HDM peptides, the Sm16 peptides, found exclusively in Schistosoma (Shiels et al ., 2020). Characterization of the Sm16 from S. mansoni showed that it was primarily expressed by cercariae and eggs, and like the CsHDM induces a pro-inflammatory response in macrophages.…”
Section: Activation Of Macrophages By Fluke-derived Moleculesmentioning
confidence: 99%
“…Remarkably, the HDM secreted by F. hepatica (FhHDM) inhibits the development of M1 macrophages, but despite being classified in the same family of peptides, the HDM secreted by C. sinensis (CsHDM) induces an M1 phenotype (Table 1; Lund et al ., 2016; Alvarado et al ., 2017; Kang et al ., 2020). Analysis of the phylogenetic relationship of the HDM peptide family shows that while CsHDM is on the same branch as FhHDM, it is evolutionarily closer to another branch of HDM peptides, the Sm16 peptides, found exclusively in Schistosoma (Shiels et al ., 2020). Characterization of the Sm16 from S. mansoni showed that it was primarily expressed by cercariae and eggs, and like the CsHDM induces a pro-inflammatory response in macrophages.…”
Section: Activation Of Macrophages By Fluke-derived Moleculesmentioning
confidence: 99%
“…Sm16 is highly expressed in cercariae and in early transformed larvae; the protein is released from cercarial acetabular glands during host penetration and can additionally be detected in the schistosomulum tegument [ 31 , 32 ]. Sm16 is expressed in eggs and sporocysts too, but not in male or female adult worms [ 33 ]. The protein is a lipid bilayer binder that forms an approximately 9-subunit oligomer and attaches to the surface of diverse cell types in a polyanion-independent manner [ 31 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protein is a lipid bilayer binder that forms an approximately 9-subunit oligomer and attaches to the surface of diverse cell types in a polyanion-independent manner [ 31 , 32 , 34 ]. Based on sequence and gene organization considerations, Sm16 has been classified as a member of the helminth defense molecule (HDM) protein family, exclusively found in trematodes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the PI3K/ Akt pathway reversed the protective effects of FhHDM-1 on β-cells, confirming a functional role for this pathway in mediating the positive effect of the peptide. 54 Interrogation of numerous parasite and mammalian genomes has established that the helminth defense molecule peptide family is unique to flatworms, 55,56 suggesting an adaptation for a specific biological function while they reside within their mammalian hosts. Testament to this host-parasite relationship, FhHDM-1 is not cytotoxic to mammalian cells, 57 and it does not induce any adverse activity in a broad range of clinically relevant pharmacology assays (unpublished data).…”
Section: The Secreted Products Of Parasitic Wormsmentioning
confidence: 99%